Protease inhibitors targeting coronavirus and filovirus entry - Zhou, Yanchen; Vedantham, Punitha; Lu, Kai; Agudelo, Juliet; Carrion, Ricardo; Nunneley, Jerritt W.; Barnard, Dale; Pöhlmann, Stefan; McKerrow, James H.; Renslo, Adam R.; Simmons, Graham (Antiviral research, 2015)
•We identify vinylsulfones as lead candidate inhibitors of Ebola virus and SARS-CoV.•K11777 inhibited Ebola virus and SARS-CoV entry in the sub-nanomolar range.•Potent inhibition correlated with the presence of a basic piperazine ring at P3.•Serine protease inhibitor and K11777 blocked coronavirus entry into caco-2 cells.•Camostat protected 6 out of ten mice from lethal infection with SARS-CoV. In order to gain entry into cells, diverse viruses, including Ebola virus, SARS-coronavirus and the emerging MERS-coronavirus, depend on activation of their envelope glycoproteins by host cell proteases. The respective enzymes are thus excellent targets for antiviral intervention. In cell culture, activation of Ebola virus, as well as SARS- and MERS-coronavirus can be accomplished by the endosomal cysteine proteases, cathepsin L (CTSL) and cathepsin B (CTSB). In addition, SARS- and MERS-coronavirus can use serine proteases localized at the cell surface, for their activation. However, it is currently unclear which protease(s) facilitate viral spread in the infected host. We report here that the cysteine protease inhibitor K11777, ((2S)-N-[(1E,3S)-1-(benzenesulfonyl)-5-phenylpent-1-en-3-yl]-2-{[(E)-4-methylpiperazine-1-carbonyl]amino}-3-phenylpropanamide) and closely-related vinylsulfones act as broad-spectrum antivirals by targeting cathepsin-mediated cell entry. K11777 is already in advanced stages of development for a number of parasitic diseases, such as Chagas disease, and has proven to be safe and effective in a range of animal models. K11777 inhibition of SARS-CoV and Ebola virus entry was observed in the sub-nanomolar range. In order to assess whether cysteine or serine proteases promote viral spread in the host, we compared the antiviral activity of an optimized K11777-derivative with that of camostat, an inhibitor of TMPRSS2 and related serine proteases. Employing a pathogenic animal model of SARS-CoV infection, we demonstrated that viral spread and pathogenesis of SARS-CoV is driven by serine rather than cysteine proteases and can be effectively prevented by camostat. Camostat has been clinically used to treat chronic pancreatitis, and thus represents an exciting potential therapeutic for respiratory coronavirus infections. Our results indicate that camostat, or similar serine protease inhibitors, might be an effective option for treatment of SARS and potentially MERS, while vinyl sulfone-based inhibitors are excellent lead candidates for Ebola virus therapeutics.